2018
DOI: 10.3390/polym10121370
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Nanocomposites Membranes with High Permittivity Based on PVA-ZnO Nanoparticles for Potential Applications in Flexible Electronics

Abstract: This study reports the optical, structural, electrical and dielectric properties of Poly (vinyl alcohol) thin films membranes with embedded ZnO nanoparticles (PVA/ZnO) obtained by the solution casting method at low temperature of deposition. Fourier Transform Infrared spectra showed the characteristics peaks, which correspond to O–H and Zn–O bonds present in the hybrid material. The X-ray diffraction patterns indicated the presence of ZnO structure into the films. The composite material showed low absorbance a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…This peak's energy gap is 3.31 eV, which confirms that this peak is related to the ZnO nanoparticles. [ 7,8,15 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This peak's energy gap is 3.31 eV, which confirms that this peak is related to the ZnO nanoparticles. [ 7,8,15 ]…”
Section: Resultsmentioning
confidence: 99%
“…The scientific community maintains considerable interest in polyvinyl alcohol (PVA) based on metal oxide nanocomposites due to its ability to combine both polymers and dopants with their properties. [ 1–15 ] These polymers have many applications in medical and engineering technology because of their mechanical, electrical, and optical properties. [ 16,17 ] ZnO‐based polymeric nanocomposite materials have attracted scientific attention because of their transparency, high electron mobility, wide bandgap (3.2 eV, at 300 K [ 18,19 ] ), and electrical properties.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PVA has been employed for various applications such as in battery components, packaging, textile applications in the microelectronic industry, electromagnetic interference applications and so on [17,18]. Several research groups reported the dielectric properties of the PVA based nanocomposites [19][20][21]. With this inspiration, in the present study PVA has been chosen as a host polymer to synthesize PVA based nanocomposites.…”
mentioning
confidence: 98%